Postgraduate education in cardiology: legal, organizational and methodical aspects - N. B. Perepech; V. D. Shurygina; E. S. Tregubova (Медицинский совет, 2013)
Medical care outcomes are largely dependent on physician's qualification. This obvious message was once again confirmed by the Government decision to significantly increase funding of the national healthcare. Medical and preventive treatment facilities (MPTF) are increasingly equipped with up-to-date facilities to ensure provision of high-tech medical care, and doctors now can prescribe a wider variety of new drugs. With the positive changes occurring in the healthcare infrastructure, the issue of staff shortage became especially acute. Wanted are specialists qualified to use new equipment safely and effectively, and capable of providing proper pharmacotherapeutic care. A vast majority of countries all over the world face staff shortage, which is especially pronounced in cardiology - the fastest growing area of medicine. Another fact speaing in favour of training relevance is that at recent global, European and Russian cardiology conferences special meetings are devoted to advanced medical training.